Proyecto de factibilidad para la creación de una empresa productora de pulpa de papaya congelada, ubicada en la ciudad de Gualaquiza, provincia de Morona Santiago y su comercialización en la ciudad de Loja - Illescas Cajamarca, María José (2023)
In the city of Gualaquiza, the papaya crop is constant during the year, so most of the time, it is wasted or serves as food for birds; in this context, we developed the idea of producing and commercializing it in the form of pulp. The objective of this research paperwork was to determine the feasibility regarding terms of market, technical, economic-financial, and profitability for developing a frozen papaya pulp production company located in the city of Gualaquiza, province of Morona Santiago, and its commercialization in the city of Loja. The research has a quantitative non-experimental approach and a qualitative descriptive approach, for which we used the deductive, inductive, simple non-experimental, and descriptive methods. The market study had an unsatisfied demand of 136,924 pounds of frozen papaya pulp; likewise, we determined an annual supply of 22,452 pounds. The technical feasibility study determined an installed capacity of 210,240 units and a utilized capability of 49,920 pieces. The legal feasibility study established the company as a Sole Proprietorship Limited Liability Company headquarters, with their location in Gualaquiza. The financial feasibility study determined an investment of; $27,624.55 for the implementation of the project, financed 63.80% in equity and 36.20% in external capital. According to the financial indicators, we obtained a net present value of $28,239.15; the internal rate of return of 43.51%; in the benefit/cost ratio, the profitability of 0.36 cents on the dollar, the capital recovery period will be two years and 14 days, and the sensitivity analysis with an increase of 24.21% and a decrease of 17.79%. According to the results obtained, we concluded the feasibility of the project, and we recommended that the proposal is under consideration.